The potential role of alternative legumes from Asinara island for multiple uses in difficult environments - Meloni M.C.; Piluzza G.; Bullitta S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Natural populations of the species Astragalus hamosus L., Lotus cytisoides L., Lotus edulis L., Lotus ornithopodioides L., Ornithopus compressus L. and Anthyllis tetraphylla L, usually neglected and regarded as unimportant species, have been examined with the aim to establish their potential role for multiple uses on difficult Mediterranean areas. Species were chosen on the basis of their adaptation to marginal environments, their origin was from stressful environments of Asinara island and of the north western Sardinian coast. Some important characters for the survival of the species in difficult and overgrazed Mediterranean areas were observed: high pods and seed production, small seed size, hardseededness, early flowering, prostrate growth. Moreover, A. tetraphylla showed interesting ornamental features. All species deserve more attention.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)